Local spread of Tn1546-like element among three species of vancomycin resistant enterococci in an intensive care unit - Milica Jovanovic; Tanja Tosic; Snezana Jovanovic; Goran Stevanovic; Mitra Drakulovic; Rajica Stosovic; Marcus Zervos (Journal of Infection in Developing Countries)
Introduction: In an intensive care unit (ICU) of the Emergency Center in the Clinical Center of Serbia, four species of vancomycin resistant enterococci (VRE) were isolated in a 17-month period mostly from blood cultures, including E. faecalis, E. faecium, E. raffinosus and E.gallinarum.